Provenance and structure of the Yancannia Formation, southern Thomson Orogen: implications for the tectono-stratigraphic evolution of the Cambro-Ordovician western Tasmanides - Wong, S.; Collins, Bill; Hack, A.; Huang, H. (Taylor & Francis Co Ltd, 2018)
© 2018 Geological Society of Australia The upper Cambrian Yancannia Formation is a small and isolated basement exposure situated in the southern Thomson Orogen, northwestern New South Wales. Understanding the geology of the Yancannia Formation is important, as it offers a rare glimpse of the composition and structure of the mostly covered basement rocks of the southern Thomson Orogen. It consists of deformed fine-grained, lithic-rich, turbiditic metasediments, suggesting deposition in a proximal, low-energy deep-marine environment. A 497 ± 13 Ma U–Pb detrital zircon date provides its maximum depositional age, the same as previously published for a tuff horizon in a correlative unit. Analysis of sedimentological, geochronological and geophysical data confirms the Yancannia Formation belongs to the Warratta Group. The Warratta Group exhibits many similarities to the Teltawongee Group in the adjacent Delamerian Orogen, including similar provenance, sedimentology and deep-water turbiditic depositional environment. Additionally, there is no sedimentological evidence for deposition of the Warratta Group following the ca 500 Ma Delamerian Orogeny, which suggests that the Warratta Group is syn-Delamerian. However, no geochronological or structural evidence for Delamerian orogenesis was observed in the Warratta Group, suggesting that the group was either unaffected by Delamerian orogenesis, or that no conclusive record remains. The provenance signature of the Warratta Group also bears strong similarities with the upper Cambrian Stawell Zone Saint Arnaud Group in the western Lachlan Orogen. Units east of Yancannia have similar provenance signatures to the Lower Ordovician Girilambone Group of the Lachlan Orogen, suggesting equivalents exist in the southern Thomson Orogen. These are likely to be the Thomson beds, deposited in a deep-marine setting outboard of the Delamerian continental margin. Structural analysis from a ~10 km, semi-continuous, across-strike section indicates a major, kilometre-scale, upright, shallow northwest-trending, doubly plunging anticline dominates the Yancannia region. This D1structure was associated with tight-to-isoclinal folding, penetrative cleavage and abundant quartz veining of probable Benambran age. Later dextral transpressional deformation (D2) produced a sporadic, weak cleavage and dextral faulting, possibly of Bindian age. Major south-directed thrusting (D3) on the adjacent Olepoloko Fault occurred in the early Carboniferous and appears to pre-date a later deformation event (D4), which was associated with kink folding.